The evolution of entrepreneurial mindsets in the digital age - Abd Rahim, Lina Nadia; Ramlee, Nur Atiqah Zakiyyah; Salleh, Nor Fazalina; Asnawi, Nini Hartini (Universiti Teknologi Mara Selangor, 2025)
With everything going digital in this modern age, the world of entrepreneurship has shifted dramatically, and so has the mindsets of those navigating it. As compared to many years ago, entrepreneurs today think differently, due to the fast pace and constant change of the digital era. This paper explores how digitalization has reshaped traditional mindset of entrepreneurs by looking at three crucial factors: digital literacy, adaptability, and network orientation. Digital literacy is the set of skills and knowledge required to use digital tools and platforms effectively. Adaptability refers to the ability to adapt and adjust strategies when technology or the market changes. Network orientation is about how entrepreneurs use digital platforms and social media to build connections, find resources, and grow their businesses, often reaching far beyond domestic markets. This paper builds on the Entrepreneurial Mindset Theory (EMT) to create a framework that reflects how entrepreneurs operate in the digital age. It addresses a clear gap in the literature by connecting digital skills with the entrepreneurial mindset, which is something many older models tend to overlook. This paper includes a detailed theoretical framework and a literature matrix to help clarify key ideas. It offers fresh insights into how entrepreneurial thinking is evolving in the digital age, and suggests directions for future research to explore these changes further.